Embedment Length of Steel Coupling Beams—Evaluation and Proposed Revision to the AISC Seismic Provisions for Ordinary Composite Coupled Walls - Kunwar, Sushil; Shahrooz, Bahram (Engineering Journal, 2025)
One of the composite systems codified in AISC 341 (2022) is composite coupled walls, which are comprised of two or more reinforced concrete structural (shear) walls linked by steel or composite coupling beams embedded in the wall piers. The embedment length is a critical factor that affects the stiffness and strength of the coupling beams—two factors that affect the overall performance of coupled walls. Past studies have examined the performance of special coupled walls in which the wall piers are heavily reinforced and typically have boundary elements. A recent series of tests focused on ordinary composite coupled walls demonstrated that the embedment length determined according to the 2022 edition of AISC 341 was insufficient to develop the target member strength. The results prompted a need to reevaluate the equation by which the embedment length is determined. Using basic principles supported by experimental data, a revised equation was developed and evaluated through numerical simulations. The revised equation results in longer embedment lengths by as much as nearly 40% for cases that would likely be encountered in practice.